The RALE score versus the CT severity score in invasively ventilated COVID-19 patients—a retrospective study comparing their prognostic capacities - Valk, CM; Zimatore, C; Mazzinari, G; Pierrakos, C; Sivakorn, C; Dechsanga, J; Grasso, S; Beenen, L; Bos, LDJ; Paulus, F; Schultz, MJ; Pisani, L (MDPI, 2022)
Background: Quantitative radiological scores for the extent and severity of pulmonary infiltrates based on chest radiography (CXR) and computed tomography (CT) scan are increasingly used in critically ill invasively ventilated patients. This study aimed to determine and compare the prognostic capacity of the Radiographic Assessment of Lung Edema (RALE) score and the chest CT Severity Score (CTSS) in a cohort of invasively ventilated patients with acute respiratory distress syndrome (ARDS) due to COVID-19. Methods: Two-center retrospective observational study, including consecutive invasively ventilated COVID-19 patients. Trained scorers calculated the RALE score of first available CXR and the CTSS of the first available CT scan. The primary outcome was ICU mortality; secondary outcomes were duration of ventilation in survivors, length of stay in ICU, and hospital-, 28-, and 90-day mortality. Prognostic accuracy for ICU death was expressed using odds ratios and Area Under the Receiver Operating Characteristic curves (AUROC). Results: A total of 82 patients were enrolled. The median RALE score (22 [15–37] vs. 26 [20–39]; p = 0.34) and the median CTSS (18 [16–21] vs. 21 [18–23]; p = 0.022) were both lower in ICU survivors compared to ICU non-survivors, although only the difference in CTSS reached statistical significance. While no association was observed between ICU mortality and RALE score (OR 1.35 [95%CI 0.64–2.84]; p = 0.417; AUC 0.50 [0.44–0.56], this was noticed with the CTSS (OR, 2.31 [1.22–4.38]; p = 0.010) although with poor prognostic capacity (AUC 0.64 [0.57–0.69]). The correlation between the RALE score and CTSS was weak (r2 = 0.075; p = 0.012). Conclusions: Despite poor prognostic capacity, only CTSS was associated with ICU mortality in our cohort of COVID-19 patients.